Neuroprotective Anesthetic Management Using Thiopental in a 17-Year-Old with Multifocal Epidural Hematoma and Impending Brain Herniation: A Case Report - Sutan Malik Maulana Syah; Buyung Hartiyo Laksono; Eko Nofiyanto; Dewi Arum Sawitri (Journal of Anesthesiology and Clinical Research, 2026)
Introduction: Epidural hematoma resulting from severe traumatic brain injury demands immediate neuroanesthetic intervention. Multifocal lesions accompanied by pneumocephalus and impending brain herniation present profound perioperative challenges requiring targeted cerebral perfusion management. Case presentation: A 17-year-old male weighing 50 kg sustained severe polytrauma, presenting with a Glasgow Coma Scale of 12 and active auditory canal bleeding. Imaging revealed multifocal epidural hematomas in the right frontotemporal (66 cc) and right parietal (43 cc) regions, alongside pneumocephalus, a 1.5 cm subfalcine herniation, and downward transtentorial herniation. The patient, classified as ASA physical status 4E, required an emergent decompressive craniotomy and concurrent facial reconstruction. A neuroprotective anesthetic strategy was deployed utilizing thiopental, fentanyl, and atracurium to minimize the cerebral metabolic rate and control intracranial pressure. Anesthesia was maintained with sevoflurane. Hemodynamics were strictly titrated to ensure optimal cerebral perfusion pressure. Following successful surgical hematoma evacuation, the patient was admitted to the intensive care unit and demonstrated an excellent neurological recovery after a five-day admission. Conclusion: Thiopental serves as a highly effective neuroprotective induction agent for severe traumatic brain injury with intracranial hypertension. Meticulous hemodynamic control and targeted reduction of cerebral metabolism are critical in preventing secondary ischemic cascades and improving functional outcomes in polytrauma patients.